Chemical Castration for Pedophiles: Study of Fiqh Problems in Indonesia - Azhari Akmal Tarigan (Al-Ahkam, 2020)
Chemical castration is a punishment against pedophiles, who have committed acts of crime that are considered an extraordinary crime. Pedophiles have ruined the future of children, with tremendous psychological and environmental impacts. This paper aims to uncover the problems of fiqh in Indonesia concerning chemical castration which has the aim of providing a deterrent effect for rape perpetrators of children. The data collection method in this study uses the literature study. There are differences in the views of legal experts with doctors. Legal experts decide on penalties for pedophiles with Law Number. 17 of 2016 concerning the Second Amendment to Law Number. 23 of 2002 concerning Protection of Children, while the Indonesian Doctors Association states reject chemical castration punishment, following the Code of Ethics as stated in the rules of the Medical Code of Ethics Assembly (MKEK) Number. 1 of 2016 concerning Chemical Castration. Fiqh experts disagree over the castration penalty for chemistry. There is no castration punishment in the fiqh, because the Prophet Muhammad forbade castration, as opposed to Islamic principles. Some fiqh experts agree that chemical castration punishment includes ta'zīr, which is a sentence handed over entirely to the legitimate government. Thus, although the castration chemical punishment has been determined, in its implementation there are problems because there are still rejections and problems according to the fiqh expert